Keberadaan Logam Berat Pb Dan Cu Pada Bycatch Perikanan Bagan Tancap Di Perairan Banyuasin, Sumatera Selatan - Putri, Wike Ayu Eka; Agustriani, Fitri; Harahap, Diny Novita Sari; Purwiyanto, Anna Ida Sunaryo; Fauziyah, Fauziyah; Meiyerani, Jeni (Universitas Bangka Belitung, 2025)
Fish and some groups of shrimps and crabs are one of the economically important biota that live in the waters. Accumulation of heavy metals in fish can affect the economic value of marine fishery products. There are several types of fish that contain heavy metals and are harmful when consumed by humans. The purpose of this study was to determine the dominant bycatch fish species and the accumulation of heavy metals Pb and Cu in the bycatch of stationary lift net Pesisir Banyuasin. This study was conducted in November 2019 and the dominant bycatch included japuh fish (Dussumieria acuta), tembang fish (Sardinella fimbriata) and parang-parang fish (Chirocentrus dorab). Samples were taken from one stationary lift net then analysed using SSA (Atomic Absorption Spectrophotometry) with 3 repetitions. The results of the analysis found the average concentration of heavy metals Pb and Cu in japuh fish was 0.65 mg/kg Pb; 0.16 mg/kg Cu. In tembang fish 0.70 mg/kg Pb and 0.03 mg/kg Cu. The parang-parang fish was 0.50 mg/kg and 0.17 mg/kg Cu. Based on the quality standards of SNI, Directorate General of Food and Drug Administration and FAO, the Pb and Cu concentrations of the three types of by-catch fish are still below the quality standard threshold and safe for human consumption.